2018
DOI: 10.1021/acs.iecr.7b04914
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale and Multiphase Model of Fixed-Bed Reactors for Fischer–Tropsch Synthesis: Optimization Study

Abstract: Our previously developed mathematical model is used for parametric sensitivity and optimization study of conventional and milliscale fixed-bed reactors (FBRs) for Fischer−Tropsch synthesis (FTS). Five indicators are chosen to analyze the influence of eight parameters on the FBRs' performance. The results show the scale of the effects caused by changing single parameter values and highlight the most important ones.Subsequently, the model is used to perform a rigorous multivariable optimization of the FBRs' perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In catalysts with standard chemical activity, intraparticle diffusion becomes relevant for particles with a diameter greater than 0.5 mm . In this regard, the choice of catalyst shape and size will also depend on intraparticle diffusion limitations, in addition to pressure drop and heat transfer considerations. , In the context of spherical catalysts composed of cobalt and iron with industrial applications, one often observes typical diameter values that exhibit variation within the range of 1 to 4 mm. ,,,, For instance, in the LTFT process, recorded intervals were taken for the effectiveness factor between 0.14 and 0.28 for diameters ranging from 2 to 4 mm, thus indicating the presence of substantial diffusion constraints …”
Section: Reactors In Ft Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In catalysts with standard chemical activity, intraparticle diffusion becomes relevant for particles with a diameter greater than 0.5 mm . In this regard, the choice of catalyst shape and size will also depend on intraparticle diffusion limitations, in addition to pressure drop and heat transfer considerations. , In the context of spherical catalysts composed of cobalt and iron with industrial applications, one often observes typical diameter values that exhibit variation within the range of 1 to 4 mm. ,,,, For instance, in the LTFT process, recorded intervals were taken for the effectiveness factor between 0.14 and 0.28 for diameters ranging from 2 to 4 mm, thus indicating the presence of substantial diffusion constraints …”
Section: Reactors In Ft Processmentioning
confidence: 99%
“…Also highlighted are those scientific works that consider the mathematical modeling and simulation of pseudohomogeneous continuous models ,,, and heterogeneous models ,, in the FT process in different dimensions and with resistance to heat and mass transfer for studying operating variables. With the development of computational tools, the study of mass, energy, and momentum transfer in these latest models through Computational Fluid Dynamics (CFD) is essential because it analyzes the system within a wide range of operating values and reduces costs by not having to manufacture new physical designs/prototypes for analysis.…”
Section: Reactors In Ft Processmentioning
confidence: 99%
“…However, there is ongoing development using mathematical models to study the optimization and parametric sensitivity of conventional and milliscale fixed‐bed reactors. This shows that in terms of operating parameters and reactor design, the optimization of Fixed bed reactor (FBR) is dependent on a selection of objective function and some constraints (such as water partial pressure and the selectivity to methane) .…”
Section: Introductionmentioning
confidence: 99%
“…8 show comparison of simulations results with experimental results obtained at the following process conditions: temperature of 493 K, total…”
mentioning
confidence: 99%
“…Recently, our group has published several papers, dealing with modeling FTS in an MTFBR, in which various aspects of reactor performance were analyzed [5][6][7][8]. The results from these investigations, performed with the same type of catalyst used in this study, showed that the formation and presence of liquid inside the reactor can severely influence several factors: diffusion limitations, which can critically influence the catalyst effectiveness and product slate [5]; heat management [6], in which the liquid phase can improve heat transfer characteristics; the overall performance of an MTFBR, which is essential for optimization of the reactor performance [7,8].…”
mentioning
confidence: 99%